Deconstructing the Myths: An Analysis of the Selected Short Stories of Tariq Rehman - Rasool, Shamshad; Hafeez, Saima; Anwar, Behzad (Pakistan Languages and Humanities Review, 2022)
The concept of discourse with its power to construct social, political or religious myths is significant in literature and in life. This research aims to undertake a Deconstructionist study of Tariq Rahman’s selected short stories to explore the way he deconstructs different established myths of his society with the help of his counter-discourse. Derrida’s theory of Deconstruction has been employed for the analysis of his three short stories: Bingo, Eid-e-Milad-un-Nabi, and The Dying Wish. It is a qualitative study with a close analysis of the text of the short stories. The analysis shows that Rahman has deconstructed many established myths of his society to provide his readers with objective lenses to perceive reality and be better informed, and to make them get rid of hypocrisy and double standards.